The First Testament in the Gospel of Matthew 1 - Aarde, Andries van (Hervormde teologiese studies, 1997)
Matthew is to be read as a narration with an ongoing plot and an open end. There is a correlation between the (post-paschal) Jesus' commission and the risen Jesus' presence in his disciples' (post-paschal) commission until the parousia. This insight amounts to the fact that the plot of Matthew is continuing after its apparent conclusion, only to be resolved in its implied continuation. The intention of the paper is to describe, against the background of the debate among Matthean scholars, the function of the use of the First Testament in the light of the above-mentioned two sequences. The term 'First Testament' in this instance is not restricted to the Hebrew canon but also includes some pseudepi-grapha which were not considered as 'outside a canon' either by the synagogue or the church, for example 1 Enoch, 2 Baruch, The lives of the prophets and Pseudo-Philo.